Effect of Sargassum Sp Effervescent on Surface Roughness of Acrylic Resin - Endang, Fitri; Syamsul, Bashierah Ikasari; Utama, Mohammad Dharma; Jubhari, Eri Hendra; Machmud, Edy; Dammar, Irfan; Launardo, Vinsensia (Indonesia Prosthodontic Association, 2021)
Background: Denture cleaning materials on the market are available in several forms, one of which is effervescent tablets. Brown algae effervescent granules (Sargassum sp) have been demonstrated in several studies as denture cleansers but it has not been proven whether these materials affect the surface roughness of acrylic resins. Purpose: Analyzing the effect of effervescent Sargassum sp and alkaline peroxide as a soaking agent on the surface roughness of acrylic resin plates. Methods: This research is a laboratory experimental study with 27 samples of acrylic resin plates divided into three groups. Group A was immersed in effervescent granules. Group B was immersed in alkaline peroxide (sodium perborate) and group C was immersed in distilled water. Immersion was carried out for 15 minutes per day and lasted for 4 consecutive days and every day each solution was replaced with a new one. Measurement of surface roughness of samples after immersion using a surface roughness tester hardness measurement using CLSM (Confocal Laser Scan Microscopy). Result: Wilcoxon's test on the Alkaline Peroxide group showed a p value of 0.008 (p 0.05 (0.285 and 0.447) which means that there is no significant difference in surface roughness values before and after immersion. Conclusion: Sargassum sp effervescent granule solution does not affect the surface roughness of the acrylic plate.